Expression of Insulinoma-Associated 2 (INSM2) in Pancreatic Islet Cells Is Regulated by the Transcription Factors Ngn3 and NeuroD1 - Cai, Tao (Endocrine Society, 2011)
The insulinoma-associated 2 (Insm2) gene is a member of the Snail/Gfi1/Insm1 transcriptional repressor superfamily. However, little is known about how the expression of human INSM2 or mouse Insm2 in neuroendocrine tissues is regulated. Here we report the expression of INSM2/Insm2 in human fetal pancreas and mouse embryos, as well as adult pancreatic islets, and its regulation by two major islet transcription factors. Mutagenesis and chromatin immunoprecipitation analysis demonstrated that the proximal E-boxes of the mouse Insm2 promoter are direct targets of neurogenin 3 and neurogenic differentiation 1 (NeuroD1). Furthermore, we found that endogenous Insm2 expression was activated in Ngn3/NeuroD1-transduced pancreatic epithelial duct cells. Our results suggest that Insm2 plays an important role in the differentiation cascade of Ngn3/NeuroD1 signaling in pancreatic islets.